Experimental Investigation of Hybrid 3D Jute/Basalt Woven Composites Subjected to Low-velocity Impact Test - Wang, Jiaxuan; Ouyang, Yiwei; Chai, Ying; Song, Yao; Gong, Xiaozhou (Journal of Research in Science and Engineering, 2025)
The aim of this study was to estimate the effect of weft blending on low-velocity impact properties. Based on whether the jute fibers have undergone alkali treatment the fabrics are systematically classified into two categories, to examine its impact on the jute fiber. The weft mixing ratio is 1:1,1:3 and 1:5. These fabrics were then converted into composite materials utilizing Vacuum Assisted Resin Transfer Molding (VARTM). An instrumented drop hammer impact test setup was employed to investigate the effects of varying impact energies (10J, 20J, and 30J). The findings revealed a notable 27% enhancement in impact resistance following an increase in jute content. This augmentation can be credited to the high flexibility and strain rate of jute fibres, which serve to prevent sudden fractures in the hybrid composite materials. Subsequent to the alkali treatment of jute, the impact strength of the resulting composite material has been observed to enhance by a range of 11% to 15%. For a more profound comprehension of the damage mechanism, the damage behaviour of the composite material following impact was investigated under a three-dimensional optical microscope. The impact surface mainly shows the separation of the yarn from the matrix, and the non-impact surface shows the fracture and resin damage of the yarn.